2020
DOI: 10.1186/s13018-020-02002-z
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence and machine learning in orthopedic surgery: a systematic review protocol

Abstract: Background Artificial intelligence (AI) and machine learning (ML) are interwoven into our everyday lives and have grown enormously in some major fields in medicine including cardiology and radiology. While these specialties have quickly embraced AI and ML, orthopedic surgery has been slower to do so. Fortunately, there has been a recent surge in new research emphasizing the need for a systematic review. The primary objective of this systematic review will be to provide an update on the advances of AI and ML in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 19 publications
1
31
0
Order By: Relevance
“…AI and computerized support, although not new to healthcare, have lately received a lot of attention within the sphere of dentistry. ese reviews covered their potential dental applications [19], success in detecting precancerous lesions and metastases [20], effectiveness in improving the quality of maxillofacial radiology [21], success in orthodontic treatment [22], and orthopedic rehabilitation [23], as well as concurrent application with virtual reality to decrease anxiety in young patients [24]. However, the aforementioned reviews did not systematically explore the current diagnostic capabilities of AI in identifying common orofacial diseases and disorders and/or the subsequently elicited pain [17].…”
Section: Introductionmentioning
confidence: 99%
“…AI and computerized support, although not new to healthcare, have lately received a lot of attention within the sphere of dentistry. ese reviews covered their potential dental applications [19], success in detecting precancerous lesions and metastases [20], effectiveness in improving the quality of maxillofacial radiology [21], success in orthodontic treatment [22], and orthopedic rehabilitation [23], as well as concurrent application with virtual reality to decrease anxiety in young patients [24]. However, the aforementioned reviews did not systematically explore the current diagnostic capabilities of AI in identifying common orofacial diseases and disorders and/or the subsequently elicited pain [17].…”
Section: Introductionmentioning
confidence: 99%
“…This study protocol is reported in accordance with the Standard Protocol Items- Recommendations for Intervention Trials (SPIRIT) criteria [ 31 , 32 ]. The complete SPIRIT checklist can be found in Supplementary data.…”
Section: Methods and Analysismentioning
confidence: 99%
“…This study protocol is reported in accordance with the Standard Protocol Items: Recommendations for Intervention Trials (SPIRIT) criteria [ 25 , 26 ].…”
Section: Methods and Analysismentioning
confidence: 99%